Peripheral Giant Cell Granuloma – A Case Report of a 9-Year-Old Male Child - Moitrayee Sharma; Mridul Kumar Sarma; Devajit Choudhury; Sindhu S Rao; BS Santosh; Asim Debnath; Muktanjalee Deka (Journal of Pharmacy and Bioallied Sciences)
“Giant cell epulis” nowadays known as “peripheral giant cell granuloma” (PGCG) is a soft tissue benign overgrowth seen in the oral cavity. It is a type of reactive exophytic lesion of gingiva whose etiology is still not specific. Peripheral giant cell lesion may not be a life-threatening condition but when the size of the lesion exceeds a certain limit it hampers day-to-day activity of the oral cavity. It may also have a psychological effect on the person. We report a case of a 9-year-old boy with a large peripheral giant cell lesion, which interfered with his chewing habits. The purpose of reporting this case is to create awareness about peripheral giant cell lesions and its treatment modality. Under general anesthesia, the soft tissue growth was excised using an electrocautery that was approximately 5.3 cm in length and 2 cm in width. The patient was reviewed on the 7th day (postoperative), followed by 10, 20, and 30 days. After this, the patient was reviewed monthly for 6 months. Healing was successful without any events. Proper history taking is mandatory before coming to a final diagnosis. Various diagnostic aids help in coming to a confirmatory diagnosis. Complete surgical excision and elimination of any irritant factor along with clearing of the base of the lesion is mandatory to avoid recurrence rate and have a complete uneventful healing.